PENGARUH DISIPLIN KERJA DAN KOMPETENSI TEKNIS TERHADAP KINERJA PEGAWAI BKPSDM LUWU TIMUR - Ahyar Haeruddin; Sulaeman Fattah; Alam Tauhid Syukur (Jurnal Administrasi Negara, 2023)
The low professionalism score of East Luwu Regency Government employees, 30.31, shows that employee professionalism is still not as expected. Based on the results of researcher interviews, a number of BKPSDM Kab. East Luwu employees that employee performance has not been optimally in line with the organization's vision and mission goals. The purpose of this study was to determine the effect of discipline on the performance of BKPSDM employees of East Luwu Regency, the effect of technical competence on the performance of BKPSDM employees of East Luwu Regency, and the joint effect of discipline and technical competence on the performance of BKPSDM employees of East Luwu Regency. The research method used is correlational design. The population in this study were all BKPSDM employees of East Luwu Regency as many as 44 people. The sampling technique was carried out using saturated sampling technique, namely sampling as a whole. Data collection methods were carried out through questionnaires and documentation.  The results of the study are Discipline has a moderate effect on the performance of BKPSDM employees of East Luwu Regency, technical competence has a moderate effect on the performance of BKPSDM employees of East Luwu Regency, and simultaneously discipline and technical competence have a moderate effect on the performance of BKPSDM employees of East Luwu Regency.